The dose-response effects of arachidonic acid on primary human skeletal myoblasts and myotubes - Brandon M. Roberts; Alexander L. Kolb; Alyssa V. Geddis; Marshall A. Naimo; Ronald W. Matheny (Taylor & Francis Group, 2023)
Background Cellular inflammatory response, mediated by arachidonic acid (AA) and cyclooxygenase, is a highly regulated process that leads to the repair of damaged tissue. Recent studies on murine C2C12 cells have demonstrated that AA supplementation leads to myotube hypertrophy. However, AA has not been tested on primary human muscle cells. Therefore, the purpose of this study was to determine whether AA supplementation has similar effects on human muscle cells. Methods Proliferating and differentiating human myoblasts were exposed to AA in a dose-dependent manner (50-0.80 µM) for 48 (myoblasts) or 72 (myotubes) hours. Cell viability was tested using a 3-(4,5-Dimethylthiazol-2-Yl)-2,5-Diphenyltetrazolium Bromide (MTT) assay and cell counting; myotube area was determined by immunocytochemistry and confocal microscopy; and anabolic signaling pathways were evaluated by western blot and RT-PCR. Results Our data show that the treatment of primary human myoblasts treated with 50 µM and 25 µM of AA led to the release of PGE2 and PGF2α at levels higher than those of control-treated cells (p < 0.001 for all concentrations). Additionally, 50 µM and 25 µM of AA suppressed myoblast proliferation, myotube area, and myotube fusion. Anabolic signaling indicated reductions in total and phosphorylated TSC2, AKT, S6, and 4EBP1 in myoblasts at 50 µM of AA (p < 0.01 for all), but not in myotubes. These changes were not affected by COX-2 inhibition with celecoxib. Conclusion Together, our data demonstrate that high concentrations of AA inhibit myoblast proliferation, myotube fusion, and myotube hypertrophy, thus revealing potential deleterious effects of AA on human skeletal muscle cell health and viability.